A prospective study of role of doppler in pregnancy and the perinatal outcome - M., Chaithra; S., Anitha G.; Suresh, Sukanya; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The development of doppler ultrasonographic technology has provided an opportunity to obtain a qualitative and quantitative assessment of maternal and foetal circulation using a non-invasive method. It has been proved by many studies that doppler has a very important role in screening of high-risk pregnancies. Objective of this study was to evaluate the role of colour doppler study in normal and high-risk pregnancy in relation to perinatal outcome. Methods: A prospective study was done including 75 women with high risk pregnancy and 75 normal pregnant women during the period October 2018 to September 2019 in hospitals attached to Bangalore Medical College and Research Institute. Doppler examination was done after recording patients’ history, clinical examination and ultrasound. Results were analysed and conclusions were made. Results: Out of the 22 patients with PIH, 20 patients had abnormal umbilical artery S/D ratio and all 22 had abnormal MCA PI. Out of 12 patients with diabetes, 10 had abnormal umbilical artery S/D ratio. All the patients with IUGR had abnormal umbilical artery S/D ratio and abnormal MCA PI. Conclusions: Colour doppler flow velocimetry done repeatedly can predict adverse foetal events with a great degree of accuracy.